THE CHALLENGES FACED BY GERIATRIC NURSES IN LONG-TERM CARE FACILITIES - Alanoud Humaidi Rakyan Alanazi, Nasser Saad Hamed Aldossary, Mohammed Omar Abdullah Al Dhirgham, Noura Tawersh Al Onezi, Faisal Marqhal Thani Alanazi, Hind Yahya Hadadi, Fadhel Mesfer Alkhathami, Muneefaa Marzouq Alenezi; Ahmed Hussain Sufyani, Hamdan Alaife Alonazi, Saud Mokhlif Alanze, Riyadh Abdullah Al Zahrani, Aljoharah Zaid Binnamshan, Aljoharah Zaid Binnamshan, Ali Mohammed Ali Haqwi (Chelonian Research Foundation, 2022)
A comprehensive assessment of qualitative evidence on nurses' self-descriptions of their end-of-life care practice has not been conducted. The objective is to compile qualitative information about the end-of-life care practices of nurses in long-term care settings for older persons. Published and unpublished research in English were searched for in the databases MEDLINE, CINAHL, PsycINFO, EMBASE, Mednar, Google Scholar, and Ichushi. Their 137 findings were categorized into 10 distinct groups and subsequently combined into three synthesized conclusions: assuming diverse roles to facilitate the dignified passing of residents, requiring resources and support to maintain professional dedication, and experiencing a discrepancy between responsibilities and authority, which impacts multidisciplinary collaboration. Nurses fulfill multifaceted duties as the healthcare providers with the greatest expertise in addressing the intricate demands of residents. Managers and politicians should provide nurses the authority to address the discrepancy and assist them in acquiring the necessary resources for end-of-life care, thereby ensuring that residents pass away with dignity. Keywords: end-of-life (EOL) care, elderly patients, review, geriatric nurses, nursing interventions.